2018
DOI: 10.1038/s41586-018-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Environment and host as large-scale controls of ectomycorrhizal fungi

Abstract: Change history: In the HTML version of this Article, author 'Filipa Cox' had no affiliation in the author list, although she was correctly associated with affiliation 3 in the PDF. In addition, the blue circles for 'oak' were missing from Extended Data Fig. 1. These errors have been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Several meteorological variables were indeed significantly reflected in the EM fungal structure, indicating that Mongolian pine-associated EM fungal communities are susceptible to climate. This finding is not new, as many reports describe the effect of several meteorological drivers on EM fungal communities ( 6 , 57 ). Moreover, previous studies have shown that precipitation is the main driving factor behind EM fungal community assembly in desert regions ( 34 , 58 ).…”
Section: Discussionmentioning
confidence: 77%
“…Several meteorological variables were indeed significantly reflected in the EM fungal structure, indicating that Mongolian pine-associated EM fungal communities are susceptible to climate. This finding is not new, as many reports describe the effect of several meteorological drivers on EM fungal communities ( 6 , 57 ). Moreover, previous studies have shown that precipitation is the main driving factor behind EM fungal community assembly in desert regions ( 34 , 58 ).…”
Section: Discussionmentioning
confidence: 77%
“…The EMF assemblages in our study showed the typical patterns known for temperate beech forests, with high diversity ( 21 , 23 , 24 ), a dominance of certain species ( 73 , 74 ) (e.g., the genera Amanita , Xerocomus , and Scleroderma in this study), and nonuniform occurrence in the tree roots. However, the 2-day N treatments were not expected to affect the fungal community structure because the colonization and establishment of new ectomycorrhizas take weeks or months rather than days ( 75 , 76 ), and shifts in fungal communities toward more nitrophilic fungi occur as a consequence of long-term exposure to high N loads ( 77 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the key importance of these ECM fungi, they occupied only 0.5% of the total diversity in the soil and 0.1% in the roots of investigated samples. Suilloid fungi represent species of early succession and, with the age of the stand, are often replaced by other ECM fungi, which leads to the fact that they become less common [ 110 , 111 ]. Besides, a higher proportion of this group of fungi is usually found after forest disturbance [ 109 ].…”
Section: Discussionmentioning
confidence: 99%